Knowledge and Acceptance of Evolution in Europe - Empirical Findings of European Cross-Country Analyses - Kuschmierz, Paul; Justus Liebig University Giessen (My University, 2022)
In modern biology, evolution is the key concept and thus, of great importance in biology education. It has repeatedly shown that representatives of different age groups or education levels have difficulties understanding evolutionary concepts. Also, research about the acceptance and rejection of evolution has come to the fore in recent decades. With the growing body of evolution education research, measurement issues complicate the situation in terms of the possibility to compare data of different surveys. Additionally, the discussion about influencing factors on acceptance of evolution like knowledge about evolution or religious faith has arisen and is still ongoing due to deviating results in publications. Three papers have been published as part of this dissertation project. All three papers focus on the measurement issues in evolution education and particularly on the unclear situation of the fragmented research situation in Europe. Paper I concentrates on a systematic literature review on the state of evolution education research in Europe while taking measurement issues into account. Findings indicate a lack of standardized assessment of acceptance of evolution and knowledge about evolution across Europe and, therefore, reasonably comparable data. Paper II introduces an updated version of an instrument (KAEVO 2.0) to measure the knowledge about such evolutionary concepts that are essential for understanding evolution. Paper III takes the findings of Paper I up and provides the first standardized European cross-country assessment of evolution acceptance and knowledge. By use of a validated, comprehensive questionnaire, the ‘Evolution Education Questionnaire (EEQ)’ that assesses evolution acceptance and knowledge, as well as influencing factors on acceptance of evolution. 11,723 first-year university students in 26 countries were surveyed. It was demonstrated that European first-year university students in biology-related as well as non-biology related study programs generally accept evolution but lack substantial knowledge about it. A multilevel model revealed religious faith as the main influencing factor on acceptance of evolution, whereas for instance, the country’s affiliation is negligible. As part of Paper III, the EEQ has been translated into 23 different languages. Overall, this dissertation expands the existing body of research on evolution education by (1) creating a systematic overview of the state of evolution education research in Europe, (2) composing an instrument based on the investigation of several sources of validity evidence to measure acceptance of evolution and knowledge about evolution comprehensively, which is currently available in 23 languages and can be easily translated into other languages by use of a standardized ready-to-use protocol, and (3) conducting the first standardized European cross-country assessment on acceptance of evolution and knowledge about evolution.
Wissen und Einstellung zur Evolution in Europa - Empirische Erkenntnisse aus europäischen ländervergleichenden Analysen
Keywords: Evolution; Acceptance; Knowledge; Europe; Religiosity; Education; Assessment; Attitude; ddc:500; ddc:570